2017
DOI: 10.1039/c7nr02264f
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt–zinc nitride on nitrogen doped carbon black nanohybrids as a non-noble metal electrocatalyst for oxygen reduction reaction

Abstract: Bimetallic nitrides are now being considered as one of the emerging advanced functional materials due to their characteristic features and remarkable physicochemical properties. Herein, we report a new crystalline bimetallic nitride (CoZnN) that belongs to the cubic crystal phase, which was successfully synthesized through direct nitridation of metallic salts as precursors. CoZnN nanoparticles were then supported on nitrogen-doped XC-72 carbon black (N-CB), and this typical CoZnN/N-CB nanohybrid discovered can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 26 publications
5
39
0
Order By: Relevance
“…The excellent activity of the VNQDs may be due to the presence of nitrogen atoms, which can lead to the shrinkage of d-band, thus increasing the electron density near the Fermi level of VN, and further improving the reduction rate of the adsorbed oxygen atoms. 53 Furthermore, it is suggested that the introduction of nitrogen atom may weaken the strong adsorption of vanadium toward ORR intermediates (such as OH, O and OOH). In addition, the nitrogen doped in graphene also negative charged the adjacent carbon atoms, which also bene¯t the ORR activity of the VNQD-NG catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…The excellent activity of the VNQDs may be due to the presence of nitrogen atoms, which can lead to the shrinkage of d-band, thus increasing the electron density near the Fermi level of VN, and further improving the reduction rate of the adsorbed oxygen atoms. 53 Furthermore, it is suggested that the introduction of nitrogen atom may weaken the strong adsorption of vanadium toward ORR intermediates (such as OH, O and OOH). In addition, the nitrogen doped in graphene also negative charged the adjacent carbon atoms, which also bene¯t the ORR activity of the VNQD-NG catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Its ORR onset potential (in 0.1 m KOH) was reported to be 0.84 V, yet its true chemical composition and the indium catalytic role remain debated. Similarly, nanohybrid Co 3 ZnN@N‐CB (carbon black) obtained via direct nitridation of metallic salts can serve as an efficient non‐noble bimetallic ORR electrocatalyst . The onset potentials for the nitride catalysts are ≈0.9 V, and the half‐wave potentials are ≈0.829 V, 30 mV less than that of commercial 20 wt% Pt/C.…”
Section: Emerging Functionalities Of Antiperovskitesmentioning
confidence: 99%
“…However, due to its expensive cost, poor durability, and CO poisoning in the reaction, 1-5 the need to explore new efficient, durable, and cheap catalysts to substitute the Pt/C is urgent. In past decades, several alternatives have been developed, such as noble metal-based nanoparticles, 5,6 non-noble metal catalysts, 7,8 and metal-free materials. 9 Heteroatom-doped carbon materials are the representatives of the metal-free materials and the mechanism of the reduction of oxygen has been widely investigated.…”
mentioning
confidence: 99%